The Moral Theology of John Paul II: A Response to Charles E. Curran - Walsh, Francis Michael (Heythrop journal, 2012)
Over a long career of teaching and writing in the area of moral theology Charles E. Curran has experienced large areas of agreement with John Paul II on issues of social justice even while in other areas of personal and sexual issues the two are in serious disagreement. This phenomenon of agreement/disagreement has suggested to Curran that the pope is guilty of using a double methodology in his moral theological writing. Curran's book, The Moral Theology of Pope John Paul II, seeks to uncover and substantiate the root of their agreements and disagreements. This article seeks to evaluate Curran's theory. This analysis is done in two parts: first, an examination of the evidence that Curran presents to support his charge against the pope, and second, an examination of the alternative possibility that it is Curran who has the double methodology rather than the pope.